The Construction of Muslim Identities in Contemporary Brazil: By Cristina Maria de Castro (trans. Rodrigo Braga Freston) (Lanham, MD: Lexington Books, 2013. 182 pages.) (American Journal of Islam and Society, 2014)
This sociological study on the plural and often contested construction of Muslimidentities in Brazil contributes to a growing scholarship on Islam and thepolitics of religious difference across the Atlantic. Focusing on two institutionsin São Paulo state – the Islamic Center of Campinas (Centro Islâmico de Campinas)and the Islamic Charity Youth League of Brazil (Liga da Juventude IslâmicaBeneficente do Brasil), located in the Brás neighborhood of São Paulocity – Cristina Maria de Castro’s book frames the negotiation of what it meansto be Muslim in Brazil and in the wider ummah not only with regard to thehistorical longue durée and plural religious field, but also in terms of genderand ethnic politics. By focusing on this “range and diversity of [an] Islamicdiaspora,”1 to use the words of Gayatri Spivak, this book will help “undo thepolitically monolithized view of Islam that rules the globe today.”Based on a doctoral dissertation at the Federal University of São Carlos(UFSCar, São Paulo state) and post-doctoral research at the International Institutefor the Study of Islam in the Modern World (Leiden University), Castro’swork also speaks to the increasing internationalization of the Braziliansocial sciences. During the twentieth century, many sociologists, anthropologists,and others in Brazil were limited by what Andrew Wimmer and NinaGlick-Schiller have criticized as “methodological nationalism,” namely, car-rying out their research within the nation’s boundaries.2 Now based at theFederal University of Minas Gerais, Castro studied Islam in Brazil with regardto not only the transnational networks, imagined or otherwise, of twoMuslim institutions located in São Paulo state, but also the equally far-flungcirculation of orientalist, Islamophobic images that members of these and ...